Cytotoxicity evaluation of self-etching dentine bonding agents in a cell culture perfusion condition - Korsuwannawong, Suwanna; Srichan, Ratchaporn; Vajrabhaya, La-ongthong (European Journal of Dentistry, 2012)
Objective: The aim of this study was to evaluate the cytotoxicity of three dentine bonding agents (G-Bond, Clearfil S3 Bond and Clearfil SE Bond X) in cell-culture perfusion.Methods: In this experiment, 8x104 TCPC SV40 cells (bovine-pulp-derived cells transfected with simian virus 40 large T-antigen) in MEM-alpha media, 20%FCS were seeded on mesh in a 6-well plate and incubated at 37 °C with 5% CO2. After 2 days, the mesh inserts were transferred to a 24-well plate and incubated in MEM-alpha media, 20%FCS with 50 μg/ml of ascorbic acid at 37 °C with 5% CO2 for 14 days. The test materials were applied to the dentine discs of dentine barrier models. Three-dimensional cell cultures in mesh and perfusion conditions were generated in this experiment. Each material, as well as the negative control (President) and the positive control (vitrebond), was tested in 5 models with the tests repeated in triplicate. The MTT assay was used to determine cell viability after the diffusion of leachable toxicity from the tested materials through the dentine discs.Results: The cell survival rate with G-Bond and Clearfil S3 Bond was 113.03 and 90.98 percent, respectively, whereas that with Clearfil SE Bond X was 111.83 percent. All three dentine bonding agents had no toxicity compared with the negative control group (P>.05).Conclusions: All three self-etching dentine-bondingagents are nontoxic. Pulp damage caused by these three bonding agents is unlikely to occur in the clinic. (Eur J Dent 2012;6:408-414)
Keywords: Cytotoxicity; MTT assay; perfusion condition; three-dimensional cell cultures